EHealth Tools to Provide Structured Assistance for Atrial Fibrillation Screening, Management, and Guideline‐Recommended Therapy in Metropolitan General Practice: The AF‐SMART Study. Issue 1 (8th January 2019) - Orchard, Jessica; Neubeck, Lis; Freedman, Ben; Li, Jialin; Webster, Ruth; Zwar, Nicholas; Gallagher, Robyn; Ferguson, Caleb; Lowres, Nicole
Abstract : Background: This eHealth implementation study aimed to evaluate strategies to promote opportunistic atrial fibrillation (AF) screening using electronic screening prompts and improve treatment using electronic decision support (EDS) software. Methods and Results: An electronic screening prompt appeared whenever an eligible patient's (aged ≥65 years, no AF diagnosis) medical record was opened in participating general practices. General practitioners and practice nurses offered screening using a smartphone ECG, with validated AF algorithm. Guideline‐based EDS was provided to assist treatment decisions. Deidentified data were collected from practices using a data extraction tool. General practices (n=8) across Sydney, Australia, screened for a median of 6 months. A total of 1805 of 11 476 (16%) eligible patients who attended were screened (44% men, mean age 75.7 years). Screening identified 19 (1.1%) new cases of AF (mean age, 79 years; mean CHA2 DS2 ‐VASc, 3.7; 53% men). General practitioners (n=30) performed 70% of all screenings (range 1–448 patients per general practitioner). The proportion of patients with AF who had CHA2 DS2 ‐VASc ≥2 for men or ≥3 for women prescribed oral anticoagulants was higher for those diagnosed during the study: 15 of 18 (83%) for screen‐detected and 39 of 46 (85%) for clinically detected, compared with 933 of 1306 (71%) patients diagnosed before the study ( P <0.001). The EDS was accessed 111 times for patients with AF and for 4 of 19 screen‐detected patients. Conclusions: The eHealth tools showed promise. Adherence to guideline‐based oral anticoagulant prescription was significantly higher in patients diagnosed during the study period, although the EDS was only used in a minority. While the proportion of eligible patients screened and EDS use was relatively low, further refinements may improve uptake in clinical practice. Clinical Trial Registration: URL: www.anzctr.org.au . Unique identifier: ACTRN12616000850471.